2007
DOI: 10.1108/08858620710773431
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationship between sales orientation‐customer orientation (SOCO) and salesperson job performance

Abstract: PurposeIn the years since Saxe and Weitz developed a scale to measure the selling orientation and customer orientation (SOCO) of a salesperson, research findings on the effect of SOCO on salesperson job performance have shown mixed results. This article aims to synthesize the findings from the empirical studies to identify the direction and the strength of this relationship. In addition, it aims to investigate the moderating effect of customer type (business or end user consumer) and type of job performance me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 50 publications
6
86
0
9
Order By: Relevance
“…This way, our study's results may also help to explain the mixed findings of previous research regarding the effect of customer orientation on salesperson performance (Jaramillo et al 2007). While some studies found a positive relationship between customer-oriented selling and salesperson performance (e.g., Boles et al 2001), others failed to do so (e.g., Howe, Hoffman, and Hardigree 1994).…”
Section: Research Issuessupporting
confidence: 60%
“…This way, our study's results may also help to explain the mixed findings of previous research regarding the effect of customer orientation on salesperson performance (Jaramillo et al 2007). While some studies found a positive relationship between customer-oriented selling and salesperson performance (e.g., Boles et al 2001), others failed to do so (e.g., Howe, Hoffman, and Hardigree 1994).…”
Section: Research Issuessupporting
confidence: 60%
“…Performance appraisal atau penilaian terhadap prestasi kerja karyawan adalah proses yang dilakukan perusahaan dalam mengevaluasi atau menilai prestasi karyawan (Flippo, 2002 Job performance adalah hasil pekerjaan yang mengacu pada pencapaian tujuan perusahaan yang diukur berdasarkan evaluasi kinerja karyawan. Jaramillo et al, (2007) menunjukkan bahwa ethical climate yang tinggi menghasilkan job performance yang lebih tinggi. Oleh karena itu, penelitian ini mengharapkan bahwa caring climate juga berpengaruh signifikan terhadap job performance dan mengusulkan hipotesis sebagai berikut: H3: Caring climate berpengaruh positif terhadap job performance.…”
Section: Job Performanceunclassified
“…Adaptive selling behavior is defined as the "altering of sales behavior during a customer interaction, or across customer interactions, based on perceived information about the nature of the selling situation" (Weitz et al 1986, p.135). The sales literature positions adaptive selling as the mediational behavior most commonly used to translate customer orientation into salesperson's performance (e.g., Guenzi et al 2014;Jaramillo et al 2007;Goad and Jaramillo 2014), and this function is reflected in our model.…”
Section: The Sales Context and Selling Behaviormentioning
confidence: 99%
“…Therefore, to ensure completeness in our model, when relevant, we also include specific mediational control to reflect relationships that have been tested and established in previous sales research and meta-analytic studies (e.g., Jaramillo et al 2007;Goad and Jaramillo 2014). In particular, we acknowledge Guenzi et al's (2014) argument that the effect of customer orientation on salesperson performance.…”
Section: The Role Of Micro-level Ethical Beliefs In Salesperson Behaviormentioning
confidence: 99%